Exploring Meaningful Learning Practice in Islamic Religious Education Subjects at Senior High School - Ibrohim, Muhammad Maulana Malik; Supriadi, Udin; Fakhruddin, Agus; Muflih, Abdillah; Ilyasa, Faisal Fauzan (Indonesian Journal of Islamic Education Studies (IJIES), 2025)
This study aims to describe the comprehensive process of meaningful learning in Islamic Religious Education (IRE). This study used a descriptive qualitative research method, with data collected through in-depth interviews, observation, and documentation. The collected data were analyzed using interactive analysis techniques, with data validation through source triangulation. The results of the study indicate that the implementation of meaningful learning has not thoroughly followed the procedural stages outlined by David Ausubel. However, the theory's core values ​​are applied in practice. In the planning stage, teachers develop learning modules, emphasizing the selection of relevant learning objectives that have a real impact on students. The implementation stage focuses on active and participatory learning that connects the material to students' daily lives. Meanwhile, learning evaluation is conducted formatively and summatively and is complemented by regular supervision to reflect on teaching effectiveness. The implications of this study indicate that implementing a contextual, flexible, and meaningful learning approach can strengthen the quality of IRE learning while also serving as a reference for curriculum development and teacher training. These findings form the basis for further research aimed at exploring the integration of learning theory with Islamic values-based educational practices.